A dualidade formal e informal na busca pelo direito à cidade : os processos de construção do espaço urbano a partir da moradia na cidade de Vitória - Landim, Indira Maria Reis Paes (2010)
It focuses on relations between the construction or reconstruction of urban space and in organization of society, demonstrating the process of spatial segregation from the house as one side of the development of cities. It characterize the production proc